Detection of the Prostate Cancer Bone Metastases: Is It Feasible to Compare 18F-fluorocholine PET/CT, 18F-fluorodeoxyglucose PET/CT and 99mTc–methyl Diphosphonate Bone Scintigraphy? - Pietrzak, Agata Karolina; Czepczynski, Rafal; Wierzchoslawska, Ewa; Cholewinski, Witold (Urology Journal, 2018)
Purpose: The objective was to compare the efficacy of 99mTc-MDP-BS, 18F-FDG-PET/CT and 18F-FCH-PET/CT in detecting bone metastases in prostate cancer patients. Materials and methods: 56 patients diagnosed with prostate cancer underwent 99mTc-methylendiphosphonates bone scintigraphy (99mTc-MDP-BS) and fluorine-18-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG-PET/CT) or fluorine-18-fluorocholine PET/CT (18F-FCH-PET/CT) within six weeks. There were 27 patients examined with 99mTc-MDP-BS + 18F-FDG (mean age 67.96 ± 9.04 years) and 29 patients examined with 99mTc-MDP-BS + 18F-FCH (mean age 73.93 ± 8.75 years). The R factor in scintigraphy and semi - quantitative analysis with Standardized Uptake Value (SUV) in the PET/CT were used using semi - automatic methods of bone lesions’ contouring. The R factor was calculated as the total count rate in bone metastasis and the total count rate in contralateral area ratio. For further analysis, the mean pixel and the total surface of lesion product in scintigraphy, the Total Lesion Glycolysis (TLG) in the 18F-FDG-PET/CT and the Total Lesion Activity (TLA) in the 18F-FCH-PET/CT were evaluated. Results: The average maximal SUV (SUVmax) value was significantly higher in patients who underwent 18F-FCH-PET/CT than in 18F-FDG-PET/CT (5.17 ± 2.24, 3.71 ± 1.56, P < .05). The R factor differences in both groups (patients who underwent BS and 18F-FDG-PET/CT, BS and 18F-FCH-PET/CT) were insignificant (1.92 ± 0.87, 2.03 ± 0.57, respectively, P > .05). There was no statistically significant correlation (Pearsons’ correlation coefficient - Rp) between the R factor and the SUVmax within examined groups (Rp = .42; P = .31) and between the R factor and the SUVmean (Rp = .43; P = .28). A high Rp between measured total surface in the BS and volume in the PET/CT of the metastatic lesion was found. In patients who underwent BS + 18F-FDG-PET/CT and BS +18F-FCH-PET/CT, Rp equaled .95 and .70. Conclusion: 99mTc-MDP-BS, 18F-FDG-PET/CT and 18F-FCH-PET/CT occurred as comparable imaging methods in bone metastases detection in the prostate cancer patients and provide complementary clinical conclusions.